2015
DOI: 10.1007/s11999-015-4342-6
|View full text |Cite
|
Sign up to set email alerts
|

What Risk Factors Are Associated With Musculoskeletal Injury in US Army Rangers? A Prospective Prognostic Study

Abstract: Background Musculoskeletal injury is the most common reason that soldiers are medically not ready to deploy. Understanding intrinsic risk factors that may place an elite soldier at risk of musculoskeletal injury may be beneficial in preventing musculoskeletal injury and maintaining operational military readiness. Findings from this population may also be useful as hypothesis-generating work for particular civilian settings such as law enforcement officers (SWAT teams), firefighters (smoke jumpers), or others i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
120
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(128 citation statements)
references
References 39 publications
3
120
0
5
Order By: Relevance
“…This finding suggests that Operators who fell in the bottom 25th percentile in multiple characteristics were at greater risk of sustaining an injury. A previous study 39 in US Army Rangers also determined that multiple risk factors increased the likelihood of sustaining an injury. Dvorak et al 38 found a similar relationship in elite-level football players: the greater the number of risk factors, the greater the proportion of injured players.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This finding suggests that Operators who fell in the bottom 25th percentile in multiple characteristics were at greater risk of sustaining an injury. A previous study 39 in US Army Rangers also determined that multiple risk factors increased the likelihood of sustaining an injury. Dvorak et al 38 found a similar relationship in elite-level football players: the greater the number of risk factors, the greater the proportion of injured players.…”
Section: Discussionmentioning
confidence: 97%
“…However, we did not find that body fat percentage was a risk factor for injury and only observed a BMI difference in the spine-injury group. Teyhen et al 39 performed a similar prospective risk factor analysis using BMI in US Army Rangers and demonstrated no difference between soldiers who sustained an injury and those who did not. This discrepancy may be due to the observed population.…”
Section: Discussionmentioning
confidence: 99%
“…[28] Though it was not associated with higher rate of knee pain in this study, it is well documented that smoking increased the risk for musculoskeletal injuries. [2930]…”
Section: Discussionmentioning
confidence: 99%
“…A total of 18 articles were included that investigated the link between FMS score and injury risk (Table 7) [17,19,27,[63][64][65][66][67][68][69][70][71][72][73][74][75][76][77]. Ten [19, 27, 64, 70-74, 76, 77] of the 18 studies reported an association between the FMS composite score and injury.…”
Section: Functional Movement Screenmentioning
confidence: 99%
“…Differences in the number of participants, length of follow-up period, and sport/occupation of participants may have contributed to the inconsistencies in strength of relationship between FMS score and injury likelihood. In contrast, eight of the identified studies found no link between FMS composite score and injury risk [17,63,[65][66][67][68][69]75]. However, three of these studies [68,69,75] utilized very small sample sizes and this may explain the lack of association between FMS score and injury.…”
Section: Functional Movement Screenmentioning
confidence: 99%